Effect of apexification on occlusal resistance of immature teeth - Lee, WooCheol (BMC Oral Health, 2020)
BACKGROUND: Strain distribution was investigated to assess the occlusal resistance alterations in immature teeth under different occlusal force. METHODS: In vitro apexification models of teeth with a funnel-shaped immature apex were obturated with mineral trioxide aggregate (MTA; ProRoot MTA) using different combinations of core materials (10/group): group 1, full-length orthograde obturation of MTA; group 2, a 5-mm MTA apical plug with a composite core; group 3, a 5-mm MTA apical plug and back-filling with warm gutta-percha. Teeth with calcium hydroxide (CH)-medicated canals and untreated teeth with normal apices were tested as controls. The teeth were arranged between two adjacent normal-apex teeth, embedded in a resin mold with a simulated periodontal ligament space. Strain data were recorded from the 3-unit teeth assembly under static compressive occlusal forces (50, 100, 200, and 300 N). Measurements were repeated 20 times for each condition, and the data were statistically analyzed. RESULTS: The immature teeth showed altered occlusal force resistance, placing increased strain on adjacent teeth. Teeth with CH-medicated canals showed significantly inferior occlusal resistance under all tested forces (P < 0.05). Application of an MTA plug with deep composite resin core resulted in significantly better stress-bearing capacity especially under forces of 50 and 300 N (P < 0.05). CONCLUSIONS: The pattern of occlusal force distribution in immature teeth differed according to the canal obturation materials used for apexification. Immature teeth with an MTA apical plug showed more favorable occlusal force resistance than those with CH-medicated canals.